Chemotherapeutic Drugs Induce ATP Release via Caspase-gated Pannexin-1 Channels and a Caspase/Pannexin-1-independent Mechanism - Boyd-Tressler, Andrea (American Society for Biochemistry and Molecular Biology, 2014)
Anti-tumor immune responses have been linked to the regulated release of ATP from apoptotic cancer cells to engage P2 purinergic receptor signaling cascades in nearby leukocytes. We used the Jurkat T cell acute lymphocytic leukemia model to characterize the role of pannexin-1 (Panx1) channels in the release of nucleotides during chemotherapeutic drug-induced apoptosis. Diverse pro-apoptotic drugs, including topoisomerase II inhibitors, kinase inhibitors, and proteosome inhibitors, induced functional activation of Panx1 channels via caspase-3-mediated cleavage of the Panx1 autoinhibitory C-terminal domain. The caspase-activated Panx1 channels mediated efflux of ATP, but also ADP and AMP, with the latter two comprising >90% of the released adenine nucleotide pool as cells transitioned from the early to late stages of apoptosis. Chemotherapeutic drugs also activated an alternative caspase- and Panx1-independent pathway for ATP release from Jurkat cells in the presence of benzyloxycarbonyl-VAD, a pan-caspase inhibitor. Comparison of Panx1 levels indicated much higher expression in leukemic T lymphocytes than in normal, untransformed T lymphoblasts. This suggests that signaling roles for Panx1 may be amplified in leukemic leukocytes. Together, these results identify chemotherapy-activated pannexin-1 channels and ATP release as possible mediators of paracrine interaction between dying tumor cells and the effector leukocytes that mediate immunogenic anti-tumor responses.